Strategies for Learning Vocabulary in and outside the Classroom - Araya Ríos, Jacqueline (2019)
An important part of learning a language is acquiring vocabulary in order to apply it to the other aspects that are studied. Language teachers can aid students in upgrading their lexical information by using strategies that will focus their attention on meaning. Lexical learning should be a constructive process focused on finding out the meaning. As students advance from one level to another in their language learning, they will expand the amount of words they understand and use. They will also broaden the amount of information they have of a particular word. Consequently, this increases their ability to communicate when it is integrated with the structures they have also learned. In this regards, Teichroew proposed that “vocabulary knowledge can best be represented as a continuum with the initial stage being recognition and the final one production” (as cited in Gass and Selinker, 2008, p. 452). ESL teachers usually employ different strategies for lexicon learning in and outside the classroom. This article discusses the role of false cognates, affixation, and the context as key vocabulary learning strategies that may enhance the learner’s competence in L2.